Case Report: diffuse entire gastrointestinal tract involvement of ALK-positive anaplastic large cell lymphoma harboring JAK-STAT pathway mutations in an adolescent with leukemoid reaction - Yang, Sizhe; Dai, Yang; Li, Qiyuan; Zhao, Sha; Deng, Xueqin; Chen, Feifan; Zhang, Yaping; Wang, Yufang; Zhang, Wenyan (Frontiers in Oncology, 2026)
Anaplastic lymphoma kinase-positive anaplastic large cell lymphoma (ALK+ ALCL) is an aggressive mature T-cell non-Hodgkin lymphoma. Its typical characteristics include positive CD30 and ALK expression detected by immunohistochemistry, and it is often accompanied by ALK gene translocation, among which the chromosomal translocation t (2;5) is the most common. This disease predominantly affects young individuals, with extranodal involvement being relatively common. However, cases involving the digestive tract are relatively rare. We report a rare case of a 14-year-old female with ALK+ALCL presenting with fever and peripheral blood leukocytosis as initial manifestations and complicated by diffuse involvement of the entire gastrointestinal tract. The patient showed significant remission having completed 4 chemotherapy sessions. In further studies, RNA sequencing confirmed the presence of NPM1::ALK gene fusion in this case; whole-exome sequencing (WES) detected somatic mutations in multiple genes of the JAK-STAT pathway (including JAK1, PTPN6, MTOR, and TYK2). It is noteworthy that such genetic alterations are more commonly observed in ALK-negative anaplastic large cell lymphoma (ALK-ALCL) but are less commonly reported in ALK+ALCL.